If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5x + 2) + -1x = 2(x + -3) Reorder the terms: 3(2 + 5x) + -1x = 2(x + -3) (2 * 3 + 5x * 3) + -1x = 2(x + -3) (6 + 15x) + -1x = 2(x + -3) Combine like terms: 15x + -1x = 14x 6 + 14x = 2(x + -3) Reorder the terms: 6 + 14x = 2(-3 + x) 6 + 14x = (-3 * 2 + x * 2) 6 + 14x = (-6 + 2x) Solving 6 + 14x = -6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 6 + 14x + -2x = -6 + 2x + -2x Combine like terms: 14x + -2x = 12x 6 + 12x = -6 + 2x + -2x Combine like terms: 2x + -2x = 0 6 + 12x = -6 + 0 6 + 12x = -6 Add '-6' to each side of the equation. 6 + -6 + 12x = -6 + -6 Combine like terms: 6 + -6 = 0 0 + 12x = -6 + -6 12x = -6 + -6 Combine like terms: -6 + -6 = -12 12x = -12 Divide each side by '12'. x = -1 Simplifying x = -1
| 3X=9X+3 | | -5/11+5/22= | | (-7b^2+12)+(-10b^2+4)= | | 6x+12=3x-24 | | 8x-5=-4x+19 | | -20z-0.6=30z+1.3 | | 7(100+10)= | | w-38-34=-21 | | c-6=-9 | | 17x-7=2-x | | 9x-77=2x | | 3(50+25)= | | 19y=76 | | 4.87=m+0.87 | | 3(x-6)=9(x-2) | | 6-4(1-2x)=-23+3x | | 23+x=33 | | -2y^2+3y=-14 | | 6.4x=0.64 | | p+.03p=154.5 | | x-3.4=3.6 | | 63=-15+x | | 6.4x=.064 | | 6-x=4-.5x | | 2x^3+16y^3=0 | | 2x-11=83 | | 63=-15+4 | | x/2-9=-5 | | 8m-5=3 | | Y-9=42 | | -9-6x+7x=7x+3x | | -8.7-5z-1.6-z=-5z+7.6 |